Multiple modular promoter elements drive graded brinker expression in response to the Dpp morphogen gradient. - Yao, L.C.; Phin, S.; Cho, J.; Rushlow, C.; Arora, K.; Warrior, R. (Development, 2008)
Morphogen gradients play fundamental roles in patterning and cell specification during development by eliciting differential transcriptional responses in target cells. In Drosophila, Decapentaplegic (Dpp), the BMP2/4 homolog, downregulates transcription of the nuclear repressor brinker (brk) in a concentration-dependent manner to generate an inverse graded distribution. Both Dpp and Brk are crucial for directing Dpp target gene expression in defined domains and the consequent execution of distinct developmental programs. Thus, determining the mechanism by which the brk promoter interprets the Dpp activity gradient is essential for understanding both Dpp-dependent patterning and how graded signaling activity can generate different responses through transcriptional repression. We have uncovered key features of the brk promoter that suggest it uses a complex enhancer logic not represented in current models. First, we find that the regulatory region contains multiple compact modules that can independently drive brk-like expression patterns. Second, each module contains binding sites for the Schnurri/Mad/Medea (SMM) complex, which mediates Dpp-dependent repression, linked to regions that direct activation. Third, the SMM repression complex acts through a distance-dependent mechanism that probably uses the canonical co-repressor C-terminal Binding Protein (CtBP). Finally, our data suggest that inputs from multiple regulatory modules are integrated to generate the final pattern. This unusual promoter organization may be necessary for brk to respond to the Dpp gradient in a precise and robust fashion.